The archaic distinction between functioning and nonfunctioning neuroendocrine neoplasms is no longer clinically relevant - Modlin, Irvin M.; Moss, Steven F.; Gustafsson, Bjorn I.; Lawrence, Ben; Schimmack, Simon; Kidd, Mark (Langenbeck's archives of surgery, 2011)
Neuroendocrine neoplasms (NENs) are increasing in incidence and prevalence. This reflects greater clinical awareness, effective imaging, and increasing pathological diagnostic recognition. Although the identification and treatment of clinical neuroendocrine syndromes are established, there is confusion when a NEN has no discernible clinical symptoms.
Gesehen am 08.09.2022